Pengaruh Pengendalian Internal Dan Kompetensi Terhadap Efektivitas Penggajian - Asep Effendi (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIE Pasundan, 2018)
The effectiveness of payroll in organizations plays an essential role in ensuring business continuity. This study aims to determine the effect of internal controls and the competencies of the efficacy of salary. The research method used is the survey method for employees of payroll systems in the company. Thirty samples were taken by purposive sampling technique at two retail companies in the city of Bandung. The data analysis technique uses the path analysis approach. The results of the study indicate that there is a significant effect of internal control and competence on payroll effectiveness. Based on these findings, the company needs to improve internal control and employee competence so that payroll effectiveness can run optimally.